2021
DOI: 10.3991/ijim.v15i17.19179
|View full text |Cite
|
Sign up to set email alerts
|

Routing Communication Inside Ad Hoc Drones Network

Abstract: The world knows a constant development of technology applied in different sectors of activities: health, factories, homes, transportation, and others, one of the big axes that take a lot of attention today is the drone’s field. To communicate information a fleet of drones can use different communication architectures: centralized communication architecture, satellite communication architecture, cellular network communication architecture and a specific AdHoc communication architecture called the UAANET drones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They showed that the AODV performs better than the OLSR for low-density and highly dynamic networks. In [12], the authors compare the performance of reactive and proactive routing protocols for applications that use HTTP, such as voice applications, database queries, and video conferencing. However, modifications are required in existing routing algorithms to apply them to 5G applications such as UAVCENs, IoTs, and the UAV ad hoc network [10].…”
Section: Related Workmentioning
confidence: 99%
“…They showed that the AODV performs better than the OLSR for low-density and highly dynamic networks. In [12], the authors compare the performance of reactive and proactive routing protocols for applications that use HTTP, such as voice applications, database queries, and video conferencing. However, modifications are required in existing routing algorithms to apply them to 5G applications such as UAVCENs, IoTs, and the UAV ad hoc network [10].…”
Section: Related Workmentioning
confidence: 99%
“…Examples of this routing protocol are Destination sequenced distance vector (DSDV) and optimized link state protocol (OLSR) [4].…”
Section: Proactive Routingmentioning
confidence: 99%
“…It is needed that in a wireless network (WN), the stations that are sharing channels of communication as the same must be offered a reasonable chance as a fair one for accessing the medium. Fairness is considered as the main issue where the whole wireless network ad hoc should tackle [1]. Unfairness takes place if few stations are grabbing the channel's bandwidth mostly whereas others are starving [2].…”
Section: Introductionmentioning
confidence: 99%